ACUTE ETHANOL DISRUPTS PHOTIC AND SEROTONERGIC CIRCADIAN CLOCK PHASE-RESETTING IN THE MOUSE - Brager, Allison J. (2011)
BACKGROUND: Alcohol abuse is associated with impaired circadian rhythms and sleep. Ethanol administration disrupts circadian clock phase-resetting, suggesting a mode for the disruptive effect of alcohol abuse on the circadian timing system. In this study, we extend previous work in C57BL/6J mice to: 1) characterize the SCN pharmacokinetics of acute systemic ethanol administration; 2) explore the effects of acute ethanol on photic and non-photic phase-resetting; and 2) determine if the SCN is a direct target for photic effects. METHODS: First, microdialysis was used to characterize the pharmacokinetics of acute i.p. injections of 3 doses of ethanol (0.5, 1.0 and 2.0 g/kg) in the mouse suprachiasmatic (SCN) circadian clock. Second, the effects of acute i.p. ethanol administration on photic phase-delays and serotonergic ([+]8-OH-DPAT-induced) phase-advances of the circadian activity rhythm were assessed. Third, the effects of reverse-microdialysis ethanol perfusion of the SCN on photic phase-resetting were characterized. RESULTS: Peak ethanol levels from the 3 doses of ethanol in the SCN occurred within 20–40 min post-injection with half-lives for clearance ranging from 0.6–1.8 hr. Systemic ethanol treatment dose-dependently attenuated photic and serotonergic phase-resetting. This treatment also did not affect basal SCN neuronal activity as assessed by Fos expression. Intra-SCN perfusion with ethanol markedly reduced photic phase-delays. CONCLUSIONS: These results confirm that acute ethanol attenuates photic phase-delay shifts and serotonergic phase-advance shifts in the mouse. This dual effect could disrupt photic and non-photic entrainment mechanisms governing circadian clock timing. It is also significant that the SCN clock is a direct target for disruptive effects of ethanol on photic shifting. Such actions by ethanol could underlie the disruptive effects of alcohol abuse on behavioral, physiological, and endocrine rhythms associated with alcoholism.